ANALISIS PEMAHAMAN TENTANG APLIKASI CIRI-CIRI GEMBALA JEMAAT BERDASARKAN YEHEZKIEL 34:12 DI JEMAAT TOUMOU TOU BANDUNG - Richard Ratu; Edison Panjaitan (Fakultas Filsafat Universitas Advent Indonesia, 2016)
One of the calling of Heavenly father for many people is a calling of serving Him.This calling is given to every human being, but every human has a right to accept orreject it. In a wide definition of serving the work of evangelism not only run bypastors in a church, but also by the teacher in the school, literature evangelismthrough books they share door to door an offices and also deacons as Stephen andPhilip in the bible also a seamstress named Dorcas share the word of God by sew thedress for the poor people. Therefore God’s people should the in everything theycould. Ezekiel 34:12 wrote “As a shepherd looks after his scattered flock when he iswith them, so will look after my sheep. I will rescue them from all the places wherethey were scattered on a day of clouds and darkness.” Based on this background sothe Identification of the problem of this research are:1. What is the feature of the good shepherd based on Ezekiel 34:12? The featureof a good Shepherd means they have to know their responsibility as the caretaker ofthe sheep. The good shepherd never compromise with their responsibility as theshepherd who always being trusted in every kind of serving.2. What the feature application of a good shepherd? They have a characteristic ofa shepherd who always keeps the right of a shepherd to the church and have integritywere prospect by the church. Keep the right means never fail.3. What is the understanding of the member of Seventh-day Adventist Church inToumou Tou Bandung about the feature of the shepherd in his daily responsibility,works, and leadership based on Ezekiel 34:12. In a leadership of a pastor/shepherd,he has to be something to follow or good example that can be imitate by the churchmember, so the church member are able to be better in serving in the church and inthe society. Pastor as a shepherd should always take care of them and find the losingand bring them back to the stable of God so they are protected their spirituality andphysical needs.